Low Phosphorus Availability Decreases Susceptibility of Tropical Primary Productivity to Droughts - D. S. Goll; E. Joetzjer; M. Huang; P. Ciais (Geophysical Research Letters)
Abstract Large uncertainties in the susceptibility of tropical forest productivity to precipitation changes hamper climate change projection. Interactions between the availabilities of water and phosphorus could theoretically either increase or decrease the susceptibility of tropical gas exchange to variation of precipitation. The inclusion of phosphorus‐water interactions in a land surface model reduces the coefficient of variance, a measure of variability, of biweekly gross primary productivity by a factor of 1.5–2.3 at three tropical forest sites in Brazil, bringing it closer to estimates from eddy covariance measurements and remote sensing. Soil drought conditions are attenuated due to 8–30% lower water consumption during wet periods in presence of phosphorus limitation. When soils are dry, plant phosphorus acquisition is impaired by reduced ion mobility, despite an increase in net phosphorus mineralization. We conclude that water‐phosphorus interactions cannot be omitted in analysis of the resilience of tropical ecosystems to precipitation changes.